STRENGTHENING SUKUK WAQF AS A SUSTAINABLE ISLAMIC FINANCIAL TOOL FOR SOCIAL WELFARE DEVELOPMENT - Muhammad Azrul Amirullah; Muhammad Akbar Hilman; Azzam Al Hanif (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
Global economic growth by 2030 is expected to be dominated by developing countries, with significant gains from countries such as China, India and Indonesia. About 8.5 per cent of the world's population or about 700 million individuals live on less than 2.15 a day, which is categorised as extreme poverty and is important for low-income countries. On the other hand, 44 per cent of the world's population or about 3.5 billion people earn less than 6.85 a day, which falls into the poverty category associated with upper-middle-income countries. Development Goals in several sectors are to face the challenge of 2030, the challenge of national progress. Waqaf is a system of giving valuable goods or assets to be taken advantage of. In this paper, the author uses a research method in the form of a library study (library research) where he uses secondary data in the form of national and international journal literature, websites that discuss waqf. The literature is selected in accordance with the theme discussed and then the data is analysed using an inductive logic paradigm. Sukuk waqf is a financial instrument based on the principles of waqf and sharia securities where this type of waqf allows the use of waqf funds to be more productive than waqf in general with stability and sustainability.